Vloga športnega pedagoga pri gibalnem razvoju otrok v predšolskem obdobju - Jaunik, Martina (Šport (Ljubljana), 2025)
A kindergarten is a very important factor in getting to know, encouraging and developing the motor abilities of preschool children. Different movement activities must be adapted to the child‘s abilities, needs and interests. The purpose of the research is to determine whether 1st-grade students who had the support of a PE teacher in kindergarten (experimental group) achieve better results in motor abilities tests than first-graders who didn’t have this kind of support (control group). The research covers 1st-grade students who attend schools in the area of Styria Region (Drava Statistical Region). The sample includes 334 first-grade students from four elementary schools (experimental group of 133 children, control group of 201 children). The data were collected in the 1st grade of a primary school, in years 2022 and 2023, measured by a SLOfit test battery, and processed by the SPSS computer program and with the help of a two-way mixed analysis of variance. According to the individual motor abilities, statistically significant differences were shown in favor of the experimental group in arm plate tapping, polygon backwards, stand and reach test, and bent arm-hang. Statistically significant differences in favor of the control group were shown in the 60-meter dash. The research has shown that a child‘s physical fitness can be improved with carefully selected programmes and the support of a PE teacher working in a kindergarten who knows the children’s movement development well, monitors their progress, starts from their acquired knowledge, and builds on it.
Keywords: 1st-grade students; gibalne sposobnosti; gibalni razvoj; motor abilities; motor development; PE teacher; Predšolska vzgoja; predšolsko obdobje; preschool period; SLOfit test battery; Športna vzgoja; športnovzgojni karton; učenci 1. razreda; Učitelji